The price of access the willingness to pay for broadband connectivity of rural households in Brgy. Guinsorongan, Catbalogan City - Patata, Eman C. (2016)
Access to internet has been increasing in the present, wherein many consumers and businesses rely on this to get information and transmit data. However, rural communities are lagging behind urban areas in broadband access and adoption rates, due to high transaction costs and perhaps profitless installation for the provider. The respondents of the study are the households of Brgy. Guinsorongan, Catbalogan City. This study investigates the usage behavior, perceptions and attitudes of the household consumers towards internet. It also seeks to determine the willingness to pay for internet services and through ordinal logistic regression, identify the significant factors that affect their willingness to pay for such service.